Possible origin of transition from symmetric to asymmetric fission - H. Paşca; A.V. Andreev; G.G. Adamian; N.V. Antonenko (Physics Letters B, 2016)
The charged distributions of fragments produced in the electromagnetic-induced fission of the even–even isotopes of Rn, Ra, Th, and U are described within an improved scission-point model and compared with the available experimental data. The three-equal-peaked charge distributions are predicted for several fissioning nuclei with neutron number N=136. The possible explanation of the transition from a symmetric fission mode to an asymmetric one around N∼136 is presented. The excitation energy dependencies of the asymmetric and symmetric fission modes are anticipated.